Informing compensatory habitat creation with experimental trials: a 3-year study of a threatened amphibian. Issue 2 (21st June 2017) - Valdez, Jose W.; Klop-Toker, Kaya; Stockwell, Michelle P.; Fardell, Loren; Clulow, Simon; Clulow, John; Mahony, Michael J.
Abstract: The creation or restoration of habitat to mitigate biodiversity loss is a common conservation strategy. Evidence-based research via an extensively monitored trial study should be undertaken prior to large-scale implementation to predict success and identify potential limiting factors. We constructed an experimental trial habitat for the threatened green and golden bell frog Litoria aurea, in Australia, to inform a broader programme of compensatory habitat creation. Individuals were released into the trial plot and a nearby natural wetland for comparison to determine if the created habitat would support their growth, survival and persistence. Half of the trial waterbodies were enclosed within an exclusion fence to separate the effects of habitat suitability from ecological processes. We found the habitat provided L. aurea with sufficient resources to grow, survive and persist for 3 years. However, no breeding occurred, and further investigations need to focus on understanding the drivers of reproduction. Although a disease outbreak occurred during the study, persistence continued for the next 2 years. This was attributed to the large number of individuals released, a strategy we recommend for future mitigation strategies to account for low survival and high turnover rates. Dispersal probably affected abundance in the unfenced areas, and landscape-level initiatives are suggested for this species. This study demonstrates that experimental trials are valuable, as they can inform future habitat management by identifying limitations that could hinder success prior to the implementation of large-scale initiatives.